Strategi Penguatan Pemahaman Pembelajaran Jarak Jauh Pada Materi Listrik DC Melalui Percobaan Berbantu Lab Virtual Phet Aplication Program dan Media Sosial Telegram - Ida Puspita (Lembaga Sosial Rumah Indonesia, 2021)
This study aims to analyze the strategy of strengthening distance learning understanding on DC electrical materials through the virtual Phet application program lab assisted experiment, and Telegram Social Media. This research is a classroom action research conducted on students of class XII science in the odd semester of the 2020/2021 academic year. The results of the study show that: 1) There is a solution for implementing experiments in distance learning; 2) Students are more enthusiastic, with indications of collecting assignments on time, all assignments given are completed by all students; 3) Students can match the final results of the experiment using the PhET circuit-construction-kit-ac with quantitative calculations using the applicable DC electrical equations. As a result, students have more confidence in the learning outcomes that have been carried out; 4) Improved learning outcomes.